Effectiveness of the Sanyin Formula Plus Chemotherapy on Survival in Women With Triple-Negative Breast Cancer: A Randomized Controlled Trial - Wu, Chunyu; Sun, Chenping; Liu, Guangyu; Qin, Yuenong; Xue, Xiaohong; Wu, Xueqing; Wang, Qun; Liu, Jin; Ye, Zhen; Li, Qiong; Qu, Wenchao; Wang, Yi; et al. (Frontiers in Oncology, 2022)
Purpose To evaluate the efficacy of the Sanyin formula (SYF) plus conventional standard chemotherapy in operable triple-negative breast cancer (TNBC) patients, a randomized controlled trial was implemented at 5 hospitals and cancer centers in China between May 23, 2016, and October 31, 2019. Materials and Methods Female patients aged 18 to 80 years with operable TNBC after definitive surgery were screened and enrolled. The exclusion criteria included metastatic disease, other tumors, or locally advanced disease. Patients were randomly divided into groups SYF plus conventional standard chemotherapy and placebo plus conventional standard chemotherapy at a ratio of 1:1. The primary endpoint of the investigation was disease-free survival (DFS), and secondary endpoints included overall survival (OS) and toxicity. Results A total of 252 operable female TNBC patients were randomized to receive SYF plus conventional standard chemotherapy (N = 127) or a placebo plus conventional standard chemotherapy (N = 125). At a median follow-up of 51 months, 5-year DFS time was longer in those assigned to SYF plus conventional standard chemotherapy compared with placebo plus conventional standard chemotherapy (94.2%vs 85.5%, hazard ratio [HR] = 0.40; 95%CI, 0.17-0.97; P = 0.034). The absolute benefit for 5-year DFS was 8.7% in the SYF plus conventional standard chemotherapy group. No statistically significant difference was observed in OS between the two groups (P = 0.23). Patients with negative node status benefited more from SYF plus conventional standard chemotherapy treatment (HR = 0.21, P-interaction = 0.013) in accordance with the exploratory subgroup analyses of DFS. Conclusions The results of the present study suggest that the traditional Chinese medicine SYF plus conventional chemotherapy regimens is an effective alternative adjuvant chemotherapy strategy for female operable TNBC patients. Clinical Trial Registration https://www.chictr.org.cn/searchproj.aspx, identifier ChiCTR-IPR-16008590.